Using depth map algorithms to improve the quality of object identification on digital stereo images - Shkapov, P M; Blagoveschensky, I G; Petryakov, A N; Blagoveschensky, V G (Journal of physics. Conference series, 2019)
For the first time experimentally investigated the use of a vision system using the technology of depth maps, infrared depth sensor, laser rangefinder, lidar to determine the relief and geometric dimensions of the object on digital stereo images, which allows continuous monitoring of the state of any process. Methods of digital image processing are presented. The main advantages of such systems are considered.